2019
DOI: 10.1063/1.5085787
|View full text |Cite|
|
Sign up to set email alerts
|

First demonstration of ARC-accelerated proton beams at the National Ignition Facility

Abstract: New short-pulse kilojoule, Petawatt-class lasers, which have recently come online and are coupled to large-scale, many-beam long-pulse facilities, undoubtedly serve as very exciting tools to capture transformational science opportunities in high energy density physics. These shortpulse lasers also happen to reside in a unique laser regime: very high-energy (kilojoule), relatively long (multi-picosecond) pulse-lengths, and large (10s of micron) focal spots, where their use in driving energetic particle beams is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Simulations suggest that the multipicosecond interaction will heat plasma electrons beyond the ponderomotive potential of the laser [24][25][26][27]. Indeed, recent experimental results have confirmed that these high energy, multipicosecond laser systems accelerate ions to maximum energies beyond those predicted by traditionally cited scaling laws [28][29][30].…”
Section: Introductionmentioning
confidence: 85%
“…Simulations suggest that the multipicosecond interaction will heat plasma electrons beyond the ponderomotive potential of the laser [24][25][26][27]. Indeed, recent experimental results have confirmed that these high energy, multipicosecond laser systems accelerate ions to maximum energies beyond those predicted by traditionally cited scaling laws [28][29][30].…”
Section: Introductionmentioning
confidence: 85%
“…When proton beams are driven by the target normal sheath acceleration (TNSA) mechanism [44] one high-energy short pulse is required per beam, and the number of short pulses available at existing facilities is very limited, with many (for example, the United Kingdom's Orion and Vulcan [45] and OMEGA EP [46] in the United States) providing two short pulses. The National Ignition Facility's Advanced Radiographic Capability system has been demonstrated with four independent beamlets [47,48] and is designed to eventually provide eight [49,50]. Thus, even numbers of projections considered "very sparse" by the wider computed tomography community (75 in Ref.…”
Section: -8 Methods For Extremely Sparse-angle Proton …mentioning
confidence: 99%
“…Efforts are still underway to increase the spatial resolution of the x-ray radiographs with point-projection short pulse wire backlighters [128,129], with the aim of taking advantage of short pulse backlighter capabilities like the advanced radiographic capability (ARC) laser system at the NIF [130] or Petawatt Aquitaine Laser (PETAL) on LMJ [131]. These additional laser beamlines, based on OPCPA (Optical Parametric Chirped Pulse Amplification) technology [132], are extremely useful for generating bright X-ray sources [130] or protons beams [133] used, for example, to probe magnetized HED plasmas [134]. The plasma universe being magnetized and turbulent, one standing question remains as to how to explain the level of the observed magnetic field in the interstellar and intracluster media (ISM and ICM, respectively).…”
Section: Turbulent Hydrodynamics For Laboratory Astrophysics and Fundmentioning
confidence: 99%